A crítica contemporânea ao dualismo metafísico alma-corpo de René Descartes - Borges, David Gonçalves (2010)
This dissertation aimed to research about the contemporary conceptions concerning the mind, using as philosophical reference René Descartes - the thinker who inaugurates the inquiries on the subject with his works "Meditations On First Philosophy" and "Treatise on the Passions of the Soul." The investigation sought to identify the main implications of Cartesian metaphysics on the philosophy of mind, and to show that the latter only became a field of study distinct from other philosophical fields since it started from criticism of the Cartesianism. In the first section an extensive presentation of the thought of René Descartes was prepared, with special emphasis on his views about the "soul" (or "mind" in contemporary terms). The second section addressed the first criticisms on dualism, as well as the objections contained in the works of Gilbert Ryle and Daniel Dennett. The third section presents non-dualistic and noneliminativistic approaches, focusing on the positions of John Searle and Antonio Damasio. It was concluded that the philosophy of mind followed a linear, gradual, and somehow inevitable development - in the latter case, keeping in mind mainly how it originated from the categories postulated initially by Descartes. Additionally, it was concluded that the path to greater success and wider potential for the advancement of cognitive science is in the union between empirical and philosophical knowledge, similar to the methodology employed by Damasio.